METHODOLOGY OF USING INNOVATIVE TECHNOLOGIES IN PHYSICAL EDUCATION OF HIGHER EDUCATION STUDENTS - Zalij, Ruslan (SWorld-Ger Conference proceedings, 2024)
The article highlights the main problems of theoretical and practical plans related to the use of educational innovations in the educational process of higher education. The relevance of using innovations as targeted changes that introduce new stable elem